Effective field theory for acoustic and pseudoacoustic phonons in solids - Esposito, Angelo; Geoffray, Emma; Melia, Thomas Edward (Physical review, 2020)
We present a relativistic effective field theory for the interaction between acoustic and gapped phonons in the limit of a small gap. We show that, while the former are the Goldstone modes associated with the spontaneous breaking of spacetime symmetries, the latter are pseudo-Goldstones associated with some (small) explicit breaking. We hence dub them “pseudoacoustic” phonons. In this first investigation, we build our effective theory for the cases of one and two spatial dimensions, two atomic species, and assuming large distance isotropy. As an illustrative example, we show how the theory can be applied to compute the total lifetime of both acoustic and pseudoacoustic phonons. This construction can find applications that range from the physics of bilayer graphene to sub-GeV dark matter detectors.